Same or different? A comparison of anthropometry, physical fitness and perceptual motor characteristics in male and female youth soccer players. Issue 1 (2nd January 2020) - O'Brien-Smith, Jade; Bennett, Kyle J. M.; Fransen, Job; Smith, Mitchell R.
ABSTRACT: Objectives : Little is known about the key performance characteristics of female players throughout adolescence, and how they compares to male players. The aim of this study was to compare performance assessments for male and female youth soccer players aged 9-18 years. Methods : Anthropometry, physical fitness, motor competence, dribbling performance and decision-making were assessed in 77 female and 182 male athletes from three developmental stages (sampling stage: 9-11y; specialisation stage: 12-14y; and investment stage: 15-18y). Results : MANOVA revealed significant interaction effects for age and sex on anthropometry, motor competence & physical fitness (p<0.001, η2p=0.131-0.216), while only main effects of sex and age were revealed for decision-making and dribbling (p<0.001, η2p=0.053-0.250). Females had better mean scores for most variables in the sampling stage, whereas males in the investment stage outperformed the females. Greater performance scores for decision-making and dribbling were evident for males at all ages. These results reveal that male and female soccer players' generic performance-related characteristics differ very little at a young age, whereas performance in soccer-specific assessments do. Conclusions : Hence, this study argues that in order to maximise the size of talent pools in soccer and increase skill development, young male and female players could train and play together until the end of the sampling stage (~12y).